VD_FINDINFO Jug / 2015 / 232 vom 21. Oktober 2014 - VD Tribunal cantonal (2014)
ÉTAT DE NÉCESSITÉ, INFRACTIONS CONTRE LE DOMAINE SECRET, ILLICÉITÉ, ERREUR SUR LES FAITSDROIT PÉNAL | 13 CP, 14 CP, 17 CP, 179ter CP